ABOUT EQUALIZATION OF EQUILIBRIUM OF RESILIENT LINE OF DRILLING COLUMN - Мойсишин, Василь Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
For drafting of vector equations of equilibrium of areas of drilling column the entered Euler-Krylov’s corners, in place of traditionally corners of Euler, new dependences are got for the calculation of curvature and twisting of resilient line. As a result of researches the closed system of common equalizations of equilibrium of arbitrary area of boring column is got and the ways of its uniting are offered.